2020
DOI: 10.3390/biology9120434
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 and Cancer: Insight into Tumor Progression and Immunity

Abstract: The involvement of inflammation in cancer progression has been the subject of research for many years. Inflammatory milieu and immune response are associated with cancer progression and recurrence. In different types of tumors, growth and metastatic phenotype characterized by the epithelial mesenchymal transition (EMT) process, stemness, and angiogenesis, are increasingly associated with intrinsic or extrinsic inflammation. Among the inflammatory mediators, prostaglandin E2 (PGE2) supports epithelial tumor agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
160
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 195 publications
(235 reference statements)
1
160
0
2
Order By: Relevance
“…PGE2 is secreted by both cancer cells and immune cells present in the TME, where it promotes the differentiation of MDSCs, from bone marrow progenitors, and DCs and their recruitment and activation, the M2 polarization of macrophages and their expression of programmed death ligand (PD-L)1. In addition, it suppresses NK anti-metastatic activity by reducing the expression of their activating receptors, stimulates the induction of Th2 cells and Tregs while inhibiting Th1 polarization, overall inducing immunosuppression (115). Besides chemokines, cytokines, and eicosanoids, an immunosuppressive role is also played by metabolites produced by cancer cells, such as adenosine.…”
Section: Cytokine and Soluble Factors-mediated Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…PGE2 is secreted by both cancer cells and immune cells present in the TME, where it promotes the differentiation of MDSCs, from bone marrow progenitors, and DCs and their recruitment and activation, the M2 polarization of macrophages and their expression of programmed death ligand (PD-L)1. In addition, it suppresses NK anti-metastatic activity by reducing the expression of their activating receptors, stimulates the induction of Th2 cells and Tregs while inhibiting Th1 polarization, overall inducing immunosuppression (115). Besides chemokines, cytokines, and eicosanoids, an immunosuppressive role is also played by metabolites produced by cancer cells, such as adenosine.…”
Section: Cytokine and Soluble Factors-mediated Mechanismsmentioning
confidence: 99%
“…Notably, chemokines such as CCL2, CCL5, CCL17, CCL18, CCL20 and CCL22, cytokines such as hepatocyte growth factor (HGF), PDGF-B, VEGF, IL-4, IL-10, prostaglandin (PG) and TGF-β and enzymes, such as Cathepsin K, cyclooxygenase-2 (COX-2), ARG1 and MMPs secreted by TAMs can directly inhibit both CD8 + and CD4 + T cell effector function as well as recruit Tregs into the tumor lesion ( 114 ). In particular, PGE2, the major product of COX-2, plays a pivotal role in BC progression, though the binding to seven transmembrane G-protein-coupled receptors expressed on several immune cell subsets ( 115 ). Inhibition of its production by unselective COX inhibitors such as aspirin or other non-steroidal anti-inflammatory drugs has been associated with a reduced risk of developing BC ( 116 ), which constitutively expresses high amounts of COX-2 ( 117 ).…”
Section: Mechanisms Of Immunosuppression In Breast Tmementioning
confidence: 99%
“…Their mechanisms in anticancer activities are not fully understood, but both COX-dependent and -independent pathways play a role. COX2-derived prostaglandin E2 (PGE2) can bind to its receptors on cancer cells and promote tumor cell proliferation, migration, angiogenesis, and chemoresistance [ 197 , 198 ]. Although the anticancer effects of many NSAIDs are attributable to inhibition of the COX2/PGE2 axis, additional mechanisms of action of NSAIDs have been characterized.…”
Section: Emerging Ros-modulating Agents With the Potential To Enhamentioning
confidence: 99%
“…Published studies indicate that the antineoplastic activities of NSAIDs can also provoke antitumor immune responses. Inhibition of PGE2, a potent immunosuppressive factor enriched in the TME, leads to improved antitumor immunity [ 198 , 218 ]. Inhibition of phosphodiesterase 5 (PDE5) activity can abrogate MDSC-mediated immune suppression [ 219 , 220 ].…”
Section: Emerging Ros-modulating Agents With the Potential To Enhamentioning
confidence: 99%
“…reported that Prostaglandin E2 can suppress IRF4 expression in T cells ( 40 ). Meanwhile, Prostaglandin E2 promotes tumor progression by inducing myeloid-derived suppressor cells ( 41 ). These studies suggest a possibility that a high level of prostaglandin E2 in the tumor microenvironment induces MDSCs development by suppressing IRF4 expression.…”
Section: Discussionmentioning
confidence: 99%